PENGARUH UKURAN PERUSAHAAN,RESIKO BISNIS DAN NET PROFIT MARGIN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Robertus Robertus (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The result of the hypothesis test showed that the size of the company, ROE and NPM simultaneously having significant influence on DER in a test using the F test that produces calculated F value of 24.094 with a significance of 0.000. the results showed that the overall jointly independent variable can significantly effect on the capital structure (DER) and suggests that the model establishedÂ  have shown good / decent models. For t test that produces t-count value for the variable size of the company amounted to 0.928, t-test and ROE amounted to 7.590 t-test variable NPM of -5.194.Keywords : Company Size, Return On Equity, Net Profit Margin and Debt Equity Ratio.